Analisa Penanganan Longsor Menggunakan Software Geoslope 2012. Studi kasus : Jalan Tol Cikopo – Palimanan (CIPALI) KM122. - Rico Iman Saputra (Jurnal Proyek Teknik Sipil, 2022)
Abstract should stand alone, means that no citation in abstract. Consider it the advertisement of your article. Abstract should tell the prospective reader what you did and highlight the key findings. Avoid using technical jargon and uncommon abbreviations. You must be accurate, brief, clear and specific. Use words which reflect the precise meaning, Abstract should be precise and honest. Please follow word limitations (100‐250 words). Keywords are the labels of your manuscript and critical to correct indexing and searching. Therefore the keywords should represent the content and highlight of your article. Use only those abbreviations that are firmly established in the field. e.g. GIS  (cambria 10 pt, italic).